3-D manipulation of a single nano-droplet on graphene with an electrowetting driving scheme: critical condition and tunability. Issue 34 (15th August 2018) - Zeng, Jian; Zhang, Shiwei; Tang, Kairui; Chen, Gong; Yuan, Wei; Tang, Yong
Abstract : The 3-D actuation of a nanoscale droplet is realized using electro-wetting driving scheme. The droplet is actuated if the saturated contact angle is reached. The droplet speed is well tuned by changing the magnitude of E -field and wettability of substrate. Abstract : The next generation of micro/nano-fluidic systems, featuring manipulation of a single nanoliter volume of a chemical reactant or bio-substance, is greatly dependent on the accurate manipulation of a single nano-droplet. In this paper, to resolve the lack of efficient methods for 3-D actuation of nano-droplets with high tunability, we proposed an electro-wetting-on-dielectric (EWOD) driving scheme on a graphene surface. The droplet could be actuated when the EWOD-saturated contact angle was reached, which determined the critical magnitude of the E -field. The droplet velocity agreed well with the v com ∼ E 1/2C–O law due to the film-detachment mechanism, which indicated the low viscous dissipation and good tunability of the proposed technique. The droplet velocity could also be tuned by changing the initial wettability of the graphene surface. Detailed examination of the liquid–solid interface revealed significant penetration of water molecules into the inner Helmholtz plane (IHP) before the induction of droplet detachment when the electric energy was converted into surface energy. For all the studied cases, the saturated contact angle served as a sufficient condition for the actuation of droplets.